From books to bytes: a systematic review of the role of Information and Communication Technology (ICT) in academic library administration / Umar Mallam Bah, A’dilah Mustafa and Moh’D Zool - Bah, Umar Mallam; Mustafa, A’dilah; Zool, Moh’D (Universiti Teknologi MARA, Perlis, 2024)
The role of Information and Communication Technology (ICT) in administration is crucial as academic libraries transition from traditional repositories to dynamic digital platforms. This Systematic Literature Review (SLR) delves into ICT's impacts and applications in academic library management. The study focused on: the mechanisms and extent of ICT adoption in administrative functions, the discernible benefits and challenges associated with the deployment of ICT; and the prospective trajectories for ICT utilisation in academic libraries. Following a rigorous review methodology, twenty-six (26) peer-reviewed articles from 2020 to 2023, sourced from ScienceDirect and Web of Science, were reviewed. Findings highlight diverse applications of ICT, ranging from operational tasks such as cataloguing and analytics to strategic responsibilities like decision-making and planning. Significantly, the study uncovers latent research gaps, especially in emerging technologies, ethical ramifications, and geographical nuances, thereby delineating avenues for future academic endeavours . Additionally, the study sheds light on the variegated nature of ICT applications, pointing to success factors, challenges including digital divides, and security concerns. Thus, the study serves as a historical evaluation and prospective guide for scholars, administrators, and policymakers, delineating the intricate interplay between technological innovation, human factors, and strategic planning in academic library administration.